A porphyrin-centred fullerene tetramer containing an N@C60 substituent. Issue 7 (18th July 2018) - Macpherson, Harry; Cornes, Stuart; Zhou, Shen; Porfyrakis, Kyriakos
Abstract : An N@C60 -containing C60 tetramer was synthesized by quadruple 1, 3-dipolar cycloaddition (Prato) reaction. This molecule demonstrates the N@C60 qubit's ability to form covalently linked arrays. Furthermore, it provides a promising scaffold with which to measure multiple qubit–qubit interactions; which must be well characterized for a functioning quantum information processing architecture.